Fraud and Corruption - Kratcoski, Peter C.; Edelbacher, Maximilian (Springer, 2018)
The concepts fraud and corruption can be defined in several ways, depending on the contexts in which the terms are being applied. One needs only to look at the history of civilizations, both those in the past and the present, to see that corruption and fraud have existed as major problems in all societies, including those that were governed under the rule of kings, tsars, military dictators, or religious rulers as well as those controlled by elected officials in democratic societies. In regard to corruption, if there are people in power position who have the opportunity to make decisions and allocate resources the opportunity for corruption exists. In short, corruption can be found in almost any organization or group that has some form of power structure, including business and commercial enterprises, public service agencies, such as the police and welfare agencies, hospitals, nursing homes, educational institutions, religious organizations, and government agencies. Corruption is defined as the misuse of power to obtain an unlawful advantage. In order to engage in corruption, an individual must hold some type of position of power that gives the person the opportunity to misuse the position to take improper actions, or to fail to take actions on matters pertaining to the responsibilities of the position. The person engaging in corruption is generally motivated by self-interests such as gaining money, a promotion, or in some cases the desire to be known as having the influence to affect the outcome of matters. To engage in a corrupt act is generally defined as a crime in most criminal codes, but corruption is also a mechanism or a vehicle to commit other crimes such as theft, embezzlement, and fraud.
Major Types, Prevention, and Control